(untitled) (Bangladesh Journal of Animal Science, 2012)
A survey was conducted to estimate the productive and reproductive performances of RCC in Rawjan, Chandanaish, Potia, Satkania and Anowara upazillas of Chittagong, Bangladesh. The farmers of the study areas holding Red Chittagong Cattle (RCC) were divided into large (>1.50 acre), medium (>1.0-1.5 acre), marginal (>0.5-1.0 acre) and landless (>0-0.5 acre) categories. Existing feeding and rearing practices, productive and reproductive performances of RCC were investigated. It was found that, most of the RCCs (82%) were reared mainly by the marginal farmers. In between May to September, there was a severe shortage of feeds and fodders for RCC. However, despite severe shortage, the farmers were not interested to cultivate fodder. The degree of shortage for feed round the year had significant variation (p<0.01) among the farmers of all categories. Similar to feed shortage, the tendency of growing non-legume crops had marked variation (P<0.01) among the farmers of all categories. Birth weight, weaning weight, daily milk yield, lactation length, calving interval, age at first service, age at first calving and gestation length were 14.5 kg, 64.6 kg, 2.1 liters, 216 days, 14 months, 2.7 years, 42 months and 279.9 days respectively. It could therefore be inferred that, productivity of RCC may be increased by improving feeding systems in the study areas. http://dx.doi.org/10.3329/bjas.v41i1.11973